Pelatihan Pembuatan Lilin Aromaterapi Berbahan Minyak Jelantah di Kelompok PKK Kendalsari Tulusrejo Lowokwaru Kota Malang: Training in the Making of Aromatherapy Candles from Waste Oil in the PKK Kendalsari Tulusrejo Lowokwaru Group, Malang City - Mufriantie, Fithri; Ibrahim, Jabal Tarik; Amir, Nur Ocvanny (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Used cooking oil is household waste often thrown away without processing because it is considered to have no economic value. Used cooking oil waste from households that are not processed correctly will cause problems for the family's health and pollution of the surrounding environment. To overcome this problem, training activities were carried out on processing used cooking oil into an economically valuable product by making aromatherapy candles. After the training, participants understand the dangers of used cooking oil and understand the material on the use of used cooking oil. The training participants were able to make aromatherapy candles from used cooking oil. Participants have the skills to process used cooking oil into economically valuable aromatherapy candles, so they have the potential to foster an entrepreneurial spirit.